Penelusuran Minat dan Bakat Olahraga Pada Siswa Sekolah Menengah Pertama di Kabupaten Batang Tahun Pelajaran 2019/2020 (Universitas Negeri Semarang, 2021)
The development of sports in the Batang Regency area is still low and less than optimal. Based on the results of POPDA SMP/MTs in 2019, Batang Regency is ranked 33 out of 35 regions in Central Java. The process of selecting children to take part in competitions only during learning and extracurricular activities. The research objective: to determine the sports talent of junior high school students in Batang Regency for the 2019/2020 academic year and its suitability with student interests. This research approach uses quantitative descriptive methods.The population in this study were junior high school students in Batang Regency. The sampling technique uses purposive sampling. Data analysis in this study using descriptive percentage. The data collection techniques used in this study were (1) the sports search aptitude test was used to determine the talents of students, (2) documentation.used to obtain a list of student names and photos during the test. From the results of the data analysis, it was found that 19.3% of the test participants had an interest in accordance with their talents and 80.7% of the test participants had an interest that was not in accordance with their talents. The conclusion is that junior high school students in Batang Regency have various sports talents, but some of this potential does not match the interests of the students.Based on the research results, the results of the suitability of sports interests and talents with the most potential for students in Batang Regency were found in volleyball.The researcher's suggestion is to optimize student achievement. With this research, he hopes that it can be an alternative for the process of scouting sports talent in Batang Regency and other areas.